УЗЛУКСИЗ ТАЪЛИМ ТИЗИМИДА КВАНТ ФИЗИКАСИНИ ЎРГАНИШ - Матжанов, Н.С. (SCIENCE and SOCIETY, 2018)
The article is devoted to the analysis of the content of quantum Physics at different levels of education, the features of teaching quantum theory, there is argumented the possibility of using computer technologies in the process of presenting the material of this topic in the course of Physics.